DETERMINANTS OF OUTPUT AND PROFITABILITY OF FISH FARMING IN OYO STATE, NIGERIA - ONI, T. S; ADEOYE, R. L. (Nigerian Journal of Fisheries, 2024)
The study examined the determinants of output and profitability of fish farming in Oyo State, Nigeria. A total of 160 respondents were selected using the sampling frame of the fish farmers available. Primary data were collected using a structured questionnaire. Both descriptive and inferential statistics were employed for the study. The mean age of respondents was 46 years. The majorities were male (65%), average years of educational attainment were 15 years of schooling, and the mean farm size of the fish farmers was 2.5 acres. The results revealed that rates of return on investment are more than 1 for fish production enterprises. This implies that for every naira invested in fish production, the farmer would realize ₦1.31 from the fish enterprise. This performance measure indicates that fish farming enterprise is viable and that the business is profitable. The determinants of output of fish farming in the study area are production system (P < 0.05), number of fingerlings (P < 0.05), quantity of feed (P < 0.05), quantity of lime (P < 0.05), quantity of fertilizer (P < 0.05), educational level (P < 0.05), income (P < 0.05) and cooperative membership (P < 0.05). The study concluded that various factors determine the output of African catfish (Clarias garipinus) farmers and that the business is profitable. The study recommends training, workshops, and seminars for African catfish farmers on how they could have easy access to land, feeds at affordable rates, and sources of funds at minimal interest rates